Post abortion family planning counseling as a tool to increase contraception use - Saka Gunay; Ertem Meliksah; Ceylan Ali; Akdeniz Nurten (BMC, 2009)
Abstract Background To describe the impact of the post-abortion family planning counseling in bringing about the contraceptive usage in women who had induced abortion in a family planning clinic. Method The Diyarbakir Office of Turkish Family Planning Association (DTFPA) is a nonprofit and nongovernmental organization which runs a family planning clinic to serve the lower socio-economic populations, in Diyarbakir-Turkey. Post abortion counseling is introduced by using proper communication skills and with using appropriate methods to women. In this study we introduced contraceptive usage of women who had induced abortion one year ago and followed by DTFPA's clinic. Results 55.3% of our clients were not using contraceptive methods before abortion. At the end of the one year, 75.9% of our followed-up clients revealed that they were using one of the modern contraceptive methods. There was no woman with IUD before induced abortion. At the end of one year 124 (52.3%) women had IUD. "A modern method was introduced immediately after abortion" was the most important factor increasing modern method usage. Conclusion Our results advocate that post-abortion counseling may be an effective tool to increase the usage of contraceptives. Improved and more qualified post-abortion family planning counseling should be an integral part of abortion services.